Alpha-Glucosidase and Alpha-Amylase Inhibitory Activities, Molecular Docking, and Antioxidant Capacities of Plectranthus ecklonii Constituents - Ninon G. E. R. Etsassala; Jelili A. Badmus; Jeanine L. Marnewick; Samuel Egieyeh; Emmanuel. I. Iwuoha; Felix Nchu; Ahmed A. Hussein (MDPI AG, 2022)
Shortage in insulin secretion or degradation of produced insulin is the principal characteristic of the metabolic disorder of diabetes mellitus (DM). However, because the current medications for the treatment of DM have many detrimental side effects, it is necessary to develop more effective antidiabetic drugs with minimal side effects. Alpha-glucosidase and alpha-amylase inhibitors are directly implicated in the delay of carbohydrate digestion. Pharmacologically, these inhibitors could be targeted for the reduction in glucose absorption rate and, subsequently, decreasing the postprandial rise in plasma glucose and the risk for long-term diabetes complications. The main objectives of this research study were to isolate different phytochemical constituents present in the methanolic extract of Plectranthusecklonii and evaluate their alpha-glucosidase and alpha-amylase inhibitory activities and antioxidant capacity. The phytochemical investigation of the methanolic extract of P. ecklonii yielded three known compounds, viz. parvifloron D, F, and G (1-3, respectively). Parvifloron G was isolated for the first time from P. ecklonii. The in vitro bio-evaluation of the methanolic extract of P. ecklonii and its isolated compounds against alpha-glucosidase showed that 3 exhibited moderate inhibitory activity with IC50 values of 41.3 ± 1.2 μg/mL. Molecular docking analysis confirmed the alpha-glucosidase inhibitory activity demonstrated by 3. Additionally, strong antioxidant capacities were demonstrated by 3 and 1 on ORAC (28726.1 ± 8.1; 3942.9.6.6 ± 0.1 µM TE/g), respectively, which were comparable with the reference antioxidant epigallocatechingallate (EGCG). Furthermore, 3 also showed strong activity on TEAC (3526.1 ± 0.6 µM TE/g), followed by 2 (1069.3 ± 2.4 µM TE/g), as well as on FRAP (1455.4 ± 2.0 µM AAE/g). The methanolic extract of P. ecklonii is a rich source of abietane diterpenes with strong antioxidant activities. This is the first scientific report on alpha-glucosidase and alpha-amylase inhibitory activities, molecular docking, and antioxidant capacities of P. ecklonii constituents.